Pemulihan Tembaga Larut secara Elektrolisis pada Limbah Larutan Tembaga-Nitrat Pengrajin Pemurnian Emas Perhiasan di Kota Makassar - Apollo Apollo; Sumardi Sumardi; Suyitno Suyitno (Politeknik Negeri Ujung Pandang, 2011)
This research is aimed to recovery of copper that has been dissolved in the copper-nitrate wastewater from gold jewelry purification, with a content concentration 5318.52 mg/l of Cu, which can be obtained pure copper powder of high economic value and can contribute to a decrease in weight metal content copper on the wastewater before discharge to urban drainage. The method used is the recovery process by electrolysis or electrowinning process that using liberation cell, which uses a single pair of stainless steel electrode with copper (SS-Cu), a single pair of graphite electrodes with copper (G-Cu), also multi pairs stainless steel electrode with copper (MSS-Cu). Single-electrode pair was examined by varying the voltage and current values at time variation of process, while for many electrode pairs by varying the process time at constant voltage and current values. The recoverable amount of copper was measured by weighing the mass changes at the cathode and the copper content test of the solution using Atomic Absorption Flame Emission Spectrophotometer. Laboratory test results show the decreasing maximum content for each pair, respectively 66.60% for the SS-Cu, 49.38% for the G-Cu, and 78.94% for the MSS-Cu. With reference to the effectiveness of multi-electrode cell liberation, there are business opportunities for wastewater treatment to find powder copper that can accompany the business of gold jewelry purification.